Pharmacogenetic assessment of tafenoquine efficacy in patients with Plasmodium vivax malaria - St Jean, PL; Koh, GCKW; Breton, JJ; Espino, FEJ; Hien, TT; Krudsood, S; Lacerda, MVG; Llanos-Cuentas, A; Lon, C; Mohammed, R; Namaik-Larp, CS; Pereira, DB; et al. (Lippincott, Williams & Wilkins, 2020)
Plasmodium vivax has the largest geographic range of human malaria species and is challenging to manage and eradicate due to its ability to establish a dormant liver stage, the hypnozoite, which can reactivate leading to relapse. Until recently, the only treatment approved to kill hypnozoites was the 8-aminoquinoline, primaquine, requiring daily treatment for 14 days. Tafenoquine, an 8-aminoquinoline single-dose treatment with activity against P. vivax hypnozoites, has recently been approved by the US Food and Drug Administration and Australian Therapeutic Goods Administration for the radical cure of P. vivax malaria in patients 16 years and older. We conducted an exploratory pharmacogenetic analysis (GSK Study 208099) to assess the role of host genome-wide variation on tafenoquine efficacy in patients with P. vivax malaria using data from three GSK clinical trials, GATHER and DETECTIVE Part 1 and Part 2. Recurrence-free efficacy at 6 and 4 months and time to recurrence up to 6 months postdosing were analyzed in 438 P. vivax malaria patients treated with tafenoquine. Among the approximately 10.6 million host genetic variants analyzed, two signals reached genome-wide significance (P value ≤ 5 × 10−8). rs62103056, and variants in a chromosome 12 intergenic region, were associated with recurrence-free efficacy at 6 and 4 months, respectively. Neither of the signals has an obvious biological rationale and would need replication in an independent population. This is the first genome-wide association study to evaluate genetic influence on response to tafenoquine in P. vivax malaria.